Okay, so by the elimination method we just add the equations together. This always works because if A=B and C=D, then A+C=B+C because we are allowed to add the same thing to both sides...

But now we can say A+C=B+D because C=D, so looking back to our original equations we can see that we just added the left side of the first equation to the left of the second and the right of the first to the right of the second....

Onto this question, the left side is 4x and the right is 0 so

divide by 4 to get x=0

Now plug x=0 into one of the given equations, I'll use the first one: so 2y=27 so y=